The real slam dunk - Richardson, Charisse K.; Palmer, Charly (Atlanta, Ga. : EnRich Communications, 2001)
Ten-year-old Marcus plans to become a professional basketball player, but when he, his twin sister, and their classmates meet a real star on a school field trip, they learn the importance of dreaming more than one career dream.
590
Keywords: Vocational guidance -- Juvenile fiction; Basketball players -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; African Americans -- Juvenile fiction; Basketball -- Fiction; School field trips -- Fiction; Role models -- Fiction; Life skills -- Fiction; African Americans -- Fiction